Transgenerational impact of DEHP on body weight of Drosophila. (April 2019) - Chen, Mei-Ying; Liu, Hsin-Ping; Cheng, Jack; Chiang, Su-Yin; Liao, Wing-Ping; Lin, Wei-Yong
Abstract: Bis(2-ethylhexyl) phthalate (DEHP) is the most typical plasticizer and an environmental endocrine disruptor (EDC). DEHP is known to influence offspring fertility, growth, and obesity. However, the role of the DEHP as a transgenerational obesogen is still controversial. In this study, we used fruit flies ( Drosophila melanogaster ) to investigate where the exposure period, doses, and exposed parental sex are critical to change the body weight of the offspring. We found long-term but not short-term, and high-dose but low-dose exposure resulted in significant change. Moreover, we found DEHP treatment on the father or mother Drosophila resulted in increased or decreased body weight of the offspring respectively. Our results demonstrated the heterogeneity of transgenerational impact of DEHP and highlighted the involvement of parental endocrine system in its role as an obesogen. Graphical abstract: Image 1 Highlights: DEHP transgenerational impact on body weight depends on: Exposure period: long-term but not short-term. Dose: high but not low. Parents' gender of DEHP exposure.